Interfaith Marriage in Judaism and Christianity: Jewish-Christian Matrimonial Unions - Murshida Khatun; Md Amirul Islam; A.K.M. Abdul Latif; Md. Habibur Rahman (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
Interfaith marriage between individuals of Jewish and Christian faiths presents unique challenges and opportunities for religious coexistence and shared values. This study examines Jewish-Christian matrimonial unions, exploring the complexities and dynamics of such relationships. By analyzing the historical, theological, and social aspects of Judaism and Christianity, this study sheds light on the varying perspectives, traditions, and concerns surrounding interfaith marriages within these faith communities. Additionally, it investigates the impact of interfaith unions on religious identity, family dynamics, and the upbringing of children. By delving into the experiences and narratives of individuals in Jewish-Christian marriages, this study provides insights into the negotiation of religious differences, the preservation of cultural heritage, and the potential for mutual understanding and respect in interfaith relationships.